Characterization of interfaces between TiCN and iron-base binders. (February 2017) - Alvaredo, P.; Roa, J.J.; Jiménez-Pique, E.; Llanes, L.; Gordo, E.
Abstract: This work includes a study of the interface between matrix and reinforcement in Fe-Ti(C, N) systems. A study of wettability and solubility between metal and ceramic phases is first performed. It combines wetting experiments at high temperature with kinetics simulation. In doing so, dense Ti(C, N) is produced by spark plasma sintering and used as substrate. On the other hand, Fe, Fe-WC and Fe-Mo2 C alloys are used as metal matrix to evaluate the influence of WC and Mo2 C carbides on the formation, composition and properties of the interface. These experiments are complemented by a micromechanical study of the interface. Hardness and elastic modulus are obtained from analysis of nanoindentation arrays in the matrix and into the reinforcement for each system. The sliding contact response at the interface (and neighboring regions) is evaluated by cross-section nanoscratches conducted at different load levels. Highlights: WC and Mo2 C influence on Fe/TiCN interface formation, composition and properties. Chemical and mechanical characterization using different complementary techniques Results obtained are the basis to tailor new metallic binders for cermets.